Modelagem e compensação da dinâmica de robôs móveis e sua aplicação em controle de formação - Martins, Felipe Nascimento (2009)
A new dynamic modeling approach for unicycle-like mobile robots is proposed, which is applied in the design of controllers for this type of robot. The dynamic model thus generated accepts linear and angular velocities as inputs, which is usual in commercial robots. Some of its properties are studied and proved, and are then used in the design of adaptive controllers that compensate for the robot dynamics while tracking a desired trajectory, following a leader or being part of a group in formation control problems. The Lyapunov theory is used on the stability analysis of the equilibrium in every case. A robustness analysis considering possible parameter variation and non-modeled disturbance is also performed. The influence of the dynamic compensation is studied, and its importance is illustrated by a performance index measured for both simulation and experimentation. Three formation control strategies with dynamic compensation are presented: one is a decentralized leader-follower control, and the other two are centralized virtual structure control. A Multi-Layer Scheme for formation control is here presented using one of the centralized formation control strategies. Such scheme is flexible in the sense that each part of the formation control problem is solved by an independent module. The proposed formation controller is capable of making the robots achieve a fixed desired formation, and to follow a desired formation having time-varying position and shape. The influence of the dynamic compensation on this formation control scheme is analyzed and illustrated through both simulation and experimental results.